Recurrent synovitis of hip and MEFV gene related arthritis in children - Farhad Salehzadeh; Mehrdad Mirzarahimi (Pediatric Rheumatology Online Journal, 2020)
Abstract Background Recurrent and relapsing arthritis has been proposed to describe a group of arthritis with recurring and periodic nature, in which the joints are intermittently involved. This study reports three non-FMF patients with heterozygous MEFV gene mutations and an extraordinary arthritis as a recurrent synovitis of hip (RSH). Methods During 16-years from 2003 to 2019 at pediatric rheumatologic clinic among 195 recorded files with chronic oligoarthritis, 3 patients with diagnosis of recurrent synovitis of hip (RSH) were reviewed thoroughly. Peripheral blood was collected from patients and the samples were screened for the 12 common MEFV gene pathogenic variants. Results This study included three patients, two female and one male with relapsing idiopathic arthritis that has been located on hip joints as a sole manifestation and pathologic findings of MEFV mutations as follow: A744S, V726A, and R761H. Conclusion On the basis of possible role of MEFV gene in different rheumatic disease, MEFV gene related arthritis may be considered as a background of RSH particularly in Mediterranean area.